e— Calculus (2021)
In this work formulate the e— calculus based on the nature of the electric charges, using Newton third law and the Coulomb law, the e— algebra and the q — e deformed algebra associating the variables ei; ej as elementary charges, and x as the conductive variable. The e— derivative is defined from a simple experiment off-on light bulb respectively. On the other hand, the e— series, the e— integral, the q — e derivatives, series and integrals and their respective convergence criteria are formulated. On the e— integrals a path or closed contour Γ (x) is established to define the e— contour integrals and finally the q — e deformed calculus and the q — e Heisenberg algebra are formulated.